Yield of upland rice cultivated under sprinkler irrigation as a function of row spacing and seed density - Crusciol, Carlos Alexandre Costa; Machado, José Ricardo; Arf, Orivaldo; Rodrigues, Ricardo Antonio Ferreira (Pesquisa Agropecuaria Brasileira, 2000)
Plant development, plant phenology, yield components and grain yield of upland rice, cv. IAC 201, submitted to three different row spacings (30, 40 and 50 cm) and densities (100, 150 and 200 viable seeds/m2) were studied. The experiment was set under field conditions in a Dark-Red Latosol, loamy texture, in Selvíria, MS, Brazil, under sprinkler irrigation conditions with water replacement tension of -0.070 MPa. The number of stalks and panicles per area increased with row spacing reduction; density of 100 viable seeds/m2 is more indicated for IAC 201 cultivated under sprinkler irrigation conditions, because seed spend is smaller; row spacing of 30 cm allowed the maximum grain yield.